Analisis Dampak Regulasi Perjanjian Kerja Waktu Tertentu (PKWT) pada Kasus PT Duta Sarana Perkasa Sesudah Undang-Undang Cipta Kerja - Annisa Nino Kifani Ritonga; Dini Febrianti; Skolastika Boru Manalu; Suci Ramadhani; Khairunnisa Khairunnisa; Nurahim Rasudin (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
Although regulated under the Job Creation Law, the practice of unilateral termination of employment that disregards workers’ rights still frequently occurs in Indonesia. The primary focus of this analysis is on the case of PT. Duta Sarana Perkasa, where workers under Fixed-Term Employment Contracts (PKWT) face issues of non-compliance with labor laws. The failure to implement the provisions of the Job Creation Law (Law No. 6 of 2023) results in workers being entitled to the status of an Indefinite-Term Employment Agreement (PKWTT). Through a literature review approach, this analysis demonstrates that the terminations that occurred did not comply with applicable legal procedures and disregarded workers’ rights, including severance pay and service awards. This analysis underscores the importance of protecting workers’ rights during the layoff process and the need to effectively enforce regulations. Consequently, the Supreme Court overturned a previous ruling that did not recognize the workers’ employment status and ordered the company to pay the workers’ violated rights, although the final decision still leaves unresolved issues regarding the exclusion of wages during the process. This analysis concludes that existing regulations are not yet fully effective in protecting workers’ welfare, underscoring the need for stricter legal oversight to ensure fairness in labor relations between employers and workers in Indonesia.